Novel management of pseudomonas biofilm-like structure in a post-pneumonectomy empyema - Gustafson, Alexandra M.; Larrain, Carolina M.; Friedman, Lindsay R.; Repkorwich, Rachel; Anidi, Ifeanyichukwu U.; Forrest, Karen M.; Fennelly, Kevin P.; Carr, Shamus R. (Frontiers in Cellular and Infection Microbiology, 2024)
We present a patient with a post-pneumonectomy empyema refractory to surgical debridement and systemic antibiotics. The patient initially presented with a bronchopleural fistula and pneumothorax secondary to tuberculosis (TB) destroyed lung, which required a pneumonectomy with Eloesser flap. Ongoing pleural infection delayed the closure of the Eloesser flap, and thoracoscopic inspection of his chest cavity revealed a green, mucous biofilm-like structure lining the postpneumonectomy pleural cavity. Cultures identified pan-susceptible Pseudomonas aeruginosa. Despite debriding this biofilm-like structure and administering systemic antibiotics, the patient continued to show persistent signs of infection and regrowth of the film. We employed a novel approach to dissolve the biofilm-like structure using intrapleural dornase alfa followed by intrapleural antibiotic washes. After 3 weeks of daily washes, repeat inspection demonstrated the biofilm-like structure had completely resolved. Resolving the pseudomonas biofilm-like structure allowed permanent closure of his chest without further need for systemic antibiotics. At follow up 3 months later, he showed no sequalae. This treatment option can be an important adjunct to improve likelihood of chest closure in patients with post-pneumonectomy empyema that resists standard treatment options due to biofilm formation.